Stem Density, Productivity, and Weed Community Dynamics in Corn-Alfalfa Intercropping - Swetabh Patel (Agronomy, 2021)
Intercropping legumes with cereals for forage production is a practical multi-cropping technique to increase yield and improve land use efficiency. In a 3-year cropping sequence, alfalfa (Medicago sativa L.) intercropped with corn (Zea mays L.) may increase overall economic yield and land sustainability over either crop alone. The objective of this study was to assess overall productivity of a corn-alfalfa intercropping system and its effect on weed community. The study was conducted near Boone, IA, USA, from 2016 to 2018 and repeated from 2017 to 2019 to assess the effect of five treatments: alfalfa only, corn only, corn intercropped with alfalfa, corn intercropped with alfalfa with prohexadione (PHX) applied to alfalfa at the V8 corn stage, and spring-seeded alfalfa (corn in the seeding year followed by planting alfalfa the following year) on system productivity. Corn grain yield decreased by 23 to 26% when intercropped with alfalfa; PHX application did not affect corn or alfalfa yield. Alfalfa stand density under corn was reduced by 36 to 68% compared with alfalfa alone in the seeding year. Alfalfa forage yield in the first production year was the same among intercropped treatments and sole alfalfa. However, spring-seeded alfalfa had two to three times less yield than other treatments. Alfalfa stem density was greater in sole alfalfa than the intercropped studies in the seeding year, with fewer stems in successive production years. Alfalfa forage yield strongly correlated with stem density, stem height, and stage at harvest in the seeding year and first harvest of the first production year. Weed density inconsistently correlated with alfalfa biomass. In conclusion, establishing alfalfa in intercropping with corn can skip alfalfa low-yielding seeding year. Based on the findings of our experiment, future research on corn-alfalfa intercropping should focus on screening drought tolerant corn hybrids with vigorous root systems. Using an early-maturing corn hybrid, coupled with management practices such as appropriate N fertilization, may improve corn yield and the chances of success for this intercropping system.